2017
DOI: 10.1016/j.molmet.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-2 promotes gallbladder refilling via a TGR5-independent, GLP-2R-dependent pathway

Abstract: ObjectiveGlucagon-like peptides (GLPs) are secreted from enteroendocrine cells in response to nutrients and bile acids and control metabolism via actions on structurally-related yet distinct G protein coupled receptors. GLP-1 regulates gut motility, appetite, islet function, and glucose homeostasis, whereas GLP-2 enhances intestinal nutrient absorption. GLP-1R agonists are used to treat diabetes and obesity, and a GLP-2R agonist is approved to treat short bowel syndrome. Unexpectedly, reports of gallbladder di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
(49 reference statements)
5
27
0
Order By: Relevance
“…Although the actions of GLP-2 are predominantly localized to the gut (7), the extraintestinal expression of the GLP-2R raises important questions surrounding the safety of therapy with GLP-2R agonists, and potential actions of teduglutide beyond the gastrointestinal tract. For example, we recently detected robust expression of the GLP-2R in gallbladder and demonstrated that administration of teduglutide markedly inhibits gallbladder emptying in mice (8). These findings, subsequently extended to human studies, are consistent with reports of increased numbers of gallbladder-related adverse events associated with teduglutide therapy (9).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the actions of GLP-2 are predominantly localized to the gut (7), the extraintestinal expression of the GLP-2R raises important questions surrounding the safety of therapy with GLP-2R agonists, and potential actions of teduglutide beyond the gastrointestinal tract. For example, we recently detected robust expression of the GLP-2R in gallbladder and demonstrated that administration of teduglutide markedly inhibits gallbladder emptying in mice (8). These findings, subsequently extended to human studies, are consistent with reports of increased numbers of gallbladder-related adverse events associated with teduglutide therapy (9).…”
Section: Introductionsupporting
confidence: 76%
“…Sections were obtained from the proximal jejunum for RNA and protein analyses. Gallbladder volume measurement was performed as described previously (8). Briefly, the gallbladder was ligated to prevent emptying and resected prior to liver manipulation.…”
Section: Blood and Tissue Collectionmentioning
confidence: 99%
“…In contrast, upon reaching the ileum (lower small bowel), BA stimulation of glucagon-like peptide-2 (GLP-2) release from intestinal L-cells stimulates gallbladder refilling and may influence satiety. 30,31 As such, BAs are emerging as a potential mechanism of improving metabolic homeostasis.…”
Section: B Ile Acid Me Tabolis M and S Ig Nalingmentioning
confidence: 99%
“…* P < 0.05 vs. placebo + L-NMMA, ** P < 0.01 vs. placebo + L-NMMA that a meal challenge with high sucrose and high fat decreased wholebody NO production and NO-mediated vascular response, strongly related to plasma TG levels 30. Further, it is noted that at least certain physiological roles of GLP-2 are not regulated by NO, such as GLP-2 promotion of gallbladder refilling 31. Lastly, use of Ted, a dipeptidyl peptidase-4 resistant analogue of GLP-2 in this study is expected to cause sustained pharmacological activation of GLP-2 receptors, which may limit extrapolation of the results to physiological effects of endogenous GLP-2.…”
mentioning
confidence: 99%